ACQUISITION OF STUDENT SCIENTIFIC INQUIRY SKILLS: CENTRALISED EXAMINATION RESULTS IN CHEMISTRY - Volkinsteine, Jelena; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
From 2011, the new educational standard in Latvia in the framework of the educational reform on the centralised examination (CE) in chemistry stipulates students to demonstrate the inquiry skills they have mastered. The purpose of this study is to find out the students’ inquiry skills by analysing the CE results in chemistry. This study addresses the following research questions: (a) To what extent are the centralised examination inquiry skills measured according to the standard outcomes? (b) What information on how students have mastered the inquiry skills in chemistry is available from the CE results for the period of 2011-2015? (c) Does measuring the inquiry skills using inquiry-based laboratory work and inquiry tasks demonstrate similar achievements? The results of the study show that the CE inquiry tasks allow examining only several inquiry skills, that students have difficulties in hypothesizing and planning the procedure. The results of the examination inquiry task (the 'hidden' part) and inquiry-based laboratory work (the part prepared by the school) differ considerably. These findings show a contradiction. On the one hand, when carrying out a inquiry-based laboratory work at school students demonstrate good inquiry skills. On the other hand, they lack the skills when solving an inquiry task during the centralised examination. This proves the insufficient skills of the teachers in organising real student scientific inquiry during lessons and failure in using the inquiry-based laboratory work record as an objective measuring tool in evaluating the student inquiry skills in the examination, which is our case.